The Role of Physical Education in Enhancing Sustainable Development Goals 2, 3, 4, and 5: Insights from Student Perceptions - Baskoro Nugroho Putro; Djoko Nugroho; Hanik Liskustyawati; Sri Santoso Sabarini; Rony Syaifullah; Indra Djati Treshaputra (Bulletin of Community Engagement, 2025)
This study investigates the role of Physical Education (PE) in advancing the Sustainable Development Goals (SDGs), with a particular focus on those related to health, education, and gender equality. Employing a mixed-methods approach, the research commenced with a Focus Group Discussion (FGD) involving three expert Physical Education teachers to identify relevant sub-SDGs supported by PE. Insights from the FGD informed the development of a questionnaire designed to assess students’ perceptions of PE’s contribution to these goals. The survey was distributed to 280 male and 452 female high school students aged 16–18. Findings indicate that both male and female students perceive PE positively in relation to SDG achievement, with average scores of 3.86 for males and 3.84 for females. Statistical analysis using the Mann-Whitney U test revealed no significant gender differences (U = 64920, p = 0.555), indicating that both genders hold similar views regarding the importance of PE in supporting SDGs. The study concludes that PE is instrumental in promoting health, education, and gender equality, thereby contributing to the realization of the SDGs, with only minimal differences in perceptions between male and female students.